Preliminary Investigation of CO2 Sequestration by Chlorella sorokiniana TH01 in Single and Sequential Photobioreactors - Do, Thi Cam Van (H. : ĐHQGHN, 2020)
Increasing accumulation of CO2 in the atmosphere mainly caused by fossil fuels combustion of human activities have resulted in adverse global warming. Therefore, searching for treatment methods for effective utilization of CO2 have received a great attention worldwide. Among various methods (e.g., adsorption, absorption, storage, membrane technologies, etc.) have been developed and applied, the sequestration of CO2 using microalgae has recently emerged as an alternatively sustainable approach. In this work, a green microalgal strain Chlorella sorokiniana TH01 was used to investigate its capability in sequestration of CO2 in laboratory scale. Results indicated that the C. sorokiniana TH01 grew well under a wide range of CO2 concentration from 0.04% to 20% with maximum growth was achieved under CO2 aeration of 15%. In a single photobioreactor (PBR) with 10 min empty bed residence time (EBRT), the C. sorokiniana TH01 only achieved CO2 fixation efficiency of 6.33% under continuous aeration of 15% CO2. Increasing number of PBRs to 15 and connected in a sequence enhanced mean CO2 fixation efficiency up to 82.64%. Moreover, the CO2 fixation efficiency was stable in the range of 78.67 to 91.34% in 10 following days of the cultivation. Removal efficiency of NO3--N and PO43--P reached 82.54 – 90.25% and 95.33 – 98.02%, respectively. Our trial data demonstrated that the C. sorokiniana TH01 strain is a promising microalgal for further research in simultaneous CO2 mitigation via CO2 sequestration from flue gas as well as nutrients recycling from wastewaters.